CORNEAL INJURY AFTER BEING STRUCK BY A PIECE OF STONE - A CASE REPORT: Poster Presentation - Case Report - General practitioner - Dianata, Dewa Ayu Ina; Suniarsih, Ni Nyoman (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal lacerations in oculi trauma are common, any disruption or trauma to the cornea will affect the person's visual acuity. Case Illustration : 50 years old man came to the eye clinic of Sanjiwani General Hospital Gianyar with pain, blurred vision, and redness in his left eye, The symptom appeared abruptly after a piece of stone struck his left eye where the stone penetration looks deep enough and touched the surface of the iris. Visual acuity of his left eye (VOS) was 6/60, and open globe injury suspicion was removed by seidel test negative. He underwent surgery for corpus alienum removal with local anesthesia. During the procedure, the stone appeared to be even with the corneal surface, making it difficult to pick it up directly, so the removal technique is to pry it from the edge. The wound is closed using the suture. One week after the procedure, the patient came for a re-evaluation examination; visual acuity was improved; VOS: 6/7.5, no sign of infection or complication. Discussion : The form of the corneal lacerations can vary, with or without globe rupture. To reduce the risk of infection, tissue necrosis, and anterior peripheral synechiae formation, it is suggested that repair should occur within 24 hours after injury. In addition, repairs within this time limit may also aim to provide comfort and reduce the pain that patients may experience. Conclusion : Immediate recognition and repair procedure of corneal injury in this patient brings good vision results with no complaints of complications.